SPATIAL DISTRIBUTION OF CHLOROPHYLL-A AND NUTRIENTS IN THE TENGAH ISLAND, KARIMUNJAWA INDONESIA - Rikha Widiaratih; Agus Anugroho Dwi Suryoputra; Gentur Handoyo; Eridhani Dharma Satya (BULLETIN OF THE MARINE GEOLOGY, 2022)
Tengah Island is located between Sintok Island and Cilik Island in Karimunjawa, Jepara Regency, Central Java. Tengah Island is one of the zones for the use of marine tourism, which has the allure of attractive spots for snorkeling and diving for tourists. Coral reefs require chlorophyll-a, which is in this case produced by zooxanthellae, as a photosynthetic pigment. The chlorophyll-a concentration is influenced by many factors, including nutrients and environmental parameters. This study aims to see the spatial distribution of chlorophyll-a on Tengah Island and its relationship to nutrients, including ammonium, phosphate, and nitrate, as well as environmental parameters, namely Total Suspended Solid (TSS), salinity, pH, Dissolve Oxygen (DO), temperature, and brightness. Chlorophyll-a is analyzed using the APHA standard (2005), while nutrient analyses for ammonium, nitrate, and phosphate employ the UV-Vis spectrophotometer and Nessler reagent, the APHA 4500-No.3-B (2017), and the APHA 4500-P B, C (2017), respectively. TSS is obtained from Sentinel-2A data processing. The correlation between each dataset was carried out by a method of statistical analysis called Principal Component Analysis (PCA). The results showed that chlorophyll-a had a close relationship with ammonium (r=0.826), brightness (r=0.492), and TSS (r=-0.979). The highest chlorophyll-a concentration of 1,063 μg/L was obtained at Station 1, which is the jetty area and the closest to the mainland. This finding is supported by maximum ammonium, sourced from domestic waste and microbial activity, and good brightness, required by chlorophyll-a for photosynthesis processes.